The microbial damage and host response framework: lesson learned from pathogenic survival trajectories and immunoinflammatory responses of Talaromyces marneffei infection - Pruksaphon, Kritsada; Amsri, Artid; Jeenkeawpieam, Juthatip; Thammasit, Patcharin; Nosanchuk, Joshua D.; Youngchim, Sirida (Frontiers in Immunology, 2024)
The adverse outcomes of fungal infection in mammalian hosts depend on the complex interactions between the host immune system and pathogen virulence-associated traits. The main clinical problems arise when the host response is either too weak to effectively eliminate the pathogen or overly aggressive, resulting in host tissue damage rather than protection. This article will highlight current knowledge regarding the virulence attributions and mechanisms involved in the dual-sided role of the host immune system in the immunopathogenesis of the thermally dimorphic fungus Talaromyces marneffei through the lens of the damage response framework (DRF) of microbial pathogenesis model.